REDD+ and the State: New Forest Politics in Costa Rica, Vietnam and Indonesia - Lederer, Markus (2020)
The objective of the paper is to shed some light on one aspect of Reducing Emissions from Deforestation and Forest Degradation (REDD+) that so far has only indirectly been at the centre of the debate, the interplay between public institutions and REDD+ practices. The paper, therefore, analyses the evolvement of REDD+ in Costa Rica, Indonesia and Vietnam asking the following three interrelated questions: 1/What have states done to make REDD+ work and have public institutions set-up the necessary infrastructure? 2/Have states changed their practice in the forest sector due to REDD+ leading to a positive out-come? 3/Has the involvement of states with REDD+ led to a strengthening of state institutions (or of civil society) as guardians of the forest? Our argument is that the infrastructure forq2 REDD + has largely been set up by public administrations and that the reach and ambition but also the capacities of the state have increased in different degrees across our case studies. We also see some first instances that REDD+ has empowered new actor coalitions, has brought in new ideas and has led to a diffusion of new and often better practices in some instances. Finally, we claim that in a few cases also some unintended consequences are visible, as REDD+ has led to reforms within public institutions (e.g. in Indonesia), while in others it has rarely changed the business as usual dynamics in the forestry sector (e.g. mostly in Vietnam and Costa Rica).